Strategi Pengembangan Kualitas UMKM Untuk Meningkatkan Perekonomian Masyarakat Dusun IV Desa Wargaluyu Kabupaten Bandung - Nenden Liska Gipari; Dina Awaliah Deswita; Mohamad Rafli Fauzi; Mohammad Akmal Baihakhi (Fisip UIN Sunan Gunung Djati Bandung, 2023)
The people of Dusun IV Wargaluyu Village have a variety of business potential originating from agricultural and plantation products. However, the efforts carried out have not been optimal, so that Micro, Small and Medium Enterprises (MSMEs) activities have not been able to develop well and expand their businesses. This has resulted in many business actors closing their businesses. The problems currently being faced by Micro, Small and Medium Enterprises (MSMEs) in Hamlet IV Wargaluyu Village are lack of capital and limited product marketing. The community service method is carried out using steps based on community empowerment (Sisdamas). The aim of this program is that it is hoped that it can build the village economy through MSMEs, improve the quality of their processed products, and create jobs for the community. The strategy that can be implemented in an effort to develop the quality of MSMEs in Dusun IV Wargaluyu Village is to provide training to MSME actors related to Branding and Social Media Marketing.